A Professional Nurse Competence Scale (PNCS): Development and psychometric testing - Jin Yun Chuang; Hui Yu Liang; Hung Da Dai; Tzu Yi Tseng; Shu Yu (BMC Nursing)
Abstract Background Nurses face significant challenges due to the rapid changes brought about by the emergence of increasingly complex clinical practices. Although many instruments have been validated for measuring nursing competence, they lack an updated and more comprehensive perspective. We aimed to develop and conduct psychometric testing of a comprehensive scale for measuring the self-perceived competence of professional nurses in clinical settings. Methods This study employed an exploratory sequential mixed methods design to develop and validate the Professional Nurses Competence Scale (PNCS) in three phases. Phase 1 (development of the PNCS) included identification domains and item generation through literature review and qualitative focus group discussions, as well as content validity assessment. Phase 2 (application of the PNCS) included examining the item quality and exploring structures of the scale with 108 registered nurses (RNs). Phase 3 (evaluation of the final PNCS version) involved confirming structures through confirmatory factor analysis (CFA), as well as assessing construct validity and internal consistency with 245 RNs. Twenty-two RNs were randomly selected for test-retest reliability of the final scale. Results During the first phase, the developed PNCS contained 68 items and tests for content validity. During the second phase, tests for homogeneity and item analysis retained 39 items, which were examined with exploratory factor analysis (EFA). The EFA produced six factors that explained 30 items. During the third phase, the six-factor structure showed an acceptable model fit in the CFA, satisfied construct validity, internal consistency and stability. Conclusions The PNCS was developed based on current clinical practices and perspectives. This scale could be used to assess self-perceived competence for professional nurses who require knowledge of clinical competence.